Digital Flip Book Based E-Modules on Financial Literacy Materials - Kusumadyahdewi, Kusumadyahdewi; Firdiansyah, Yhadi (Letters in Information Technology Education (LITE), 2022)
Financial literacy is very much needed with the rise of financial products and financial service institutions that are currently available both online and offline. Consumers must have financial knowledge so that they can make good use of it, and not fall into financial problems easily. Financial literacy is focused on financial planning, banking, insurance and investment according to the circular of the Financial Services Authority (OJK) to the public. Students as human beings who are prepared to face a financially independent life, must also be equipped with financial literacy so that they can utilize financial products in their financial planning. Therefore, it is very important to compile modules for students who are currently inseparable from their smartphones and laptops. This e-module can be accessed anytime and anywhere with the gadget you have, both online and offline. The research method used is R & D from Sugiyono which consists of 10 stages. This study develops learning media in the form of e-modules for students and assesses the feasibility of media experts, material experts and students as users. The media expert's assessment resulted in 92.85, from material experts 95.31 and small group students 90.5 while the large group was 88.74 which all showed very valid categories. This shows that the e-module is acceptable and appropriate to be given to students for the Financial Management course on Financial Literacy.